Impact of forest harvesting intensity and water table on biodegradability of dissolved carbon in boreal peat in an incubation experiment - Peltomaa, Elina; Könönen, Mari; Palviainen, Marjo; Lauren, Annamari (Ari); Zhu, Xudan; Kinnunen, Niko; Aaltonen, Heidi; Ojala, Anne; Pumpanen, Jukka (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Boreal peatlands are vast carbon (C) stores but also major sources of dissolved organic C (DOC) and nutrients to surface waters. Drainage and forest harvesting accelerates DOC leaching. Continuous cover forestry (CCF) is considered to cause fewer adverse environmental effects. Yet, the effects of CCF on DOC processes are unrecognised. We study DOC production and quality in unharvested, CCF, and clear-cut drained peatland forests and in a non-forested alluvial sedge fen. Parallel replicate peat columns with ground vegetation are collected from the uppermost 50 cm at each site, and the water table (WT) is set to −20 or −40 cm depths on the columns. During the eight-month ex situ incubation experiment, the soil water samples are extracted monthly or bi-monthly. The samples are incubated at 15 °C for multiple 72 h incubation cycles to study pore water quality and biodegradation of DOC. The CO2 production occurs during the first three days. The DOC concentrations and the CO2 release per volume of water are significantly lower in the sedge fen than in the drained peatland forests. The WT has a negligible effect on DOC concentrations and no effect on DOC quality, but the higher WT has generally higher CO2 production per DOC than the lower WT. The results suggest that peat in the drained peatlands is not vulnerable to changes per se but that forest management alters biotic and abiotic factors that control the production, transport, and biodegradation of DOC.
Keywords: forest management; peatland forestry; continuous cover forestry; clear-cutting; dissolved organic carbon (DOC); biodegradability; water quality; drainage